A contracepção nas páginas da Capricho - os discursos concernentes à contracepção reverberados pela revista Capricho no ano de 1994 - Galcowski, Anderson Nereu (2011)
This research aims to recognize the discourse concerning contraceptive practices conveyed by Capricho magazine in 1994. To that end, was organized a set of sources consisting of six volumes of the magazine of the months: January, March, May, September, October, December in the same year. It includes a description of the historical path of contraception in Brazil since the sixties to the mid-nineties, including from the perspective that encompasses public policies about the use of hormonal contraceptives and condoms. It seeks to analyzes some concepts related to cultural pedagogy and its related areas and to investigate the possible ways in which discourses propagated by the media interfere in the formation of subjectivities.